Prediksi Persediaan Bahan Baku untuk Produksi Percetakan Menggunakan Metode Asosiasi - Agus Junaidi; Alif Rahman; Yunita Yunita (LPPM Universitas Bina Sarana Informatika, 2021)
The use of technology in the offset printing industry is now making it faster for users to get production results. Another advantage of the offset printing industry is high quality printing, consistent color printing and low cost for large volume printing. The offset printing industry is one of the industries that have the most frequent ordering of raw materials, this is due to the pattern of consumers who order more than one type of paper. Therefore, the unavailability of raw materials can cause the order to be constrained. By using this association method, it can be seen the amount of paper raw material needed to complete a product in the future so that the company can optimize the supply of raw materials needed so that the amount of inventory is not too much but not too little. In this study the support used has a threshold of more than 20% and a minimum confidence 30%. With these results can be optimized in the subsequent ordering of raw materials for paper and can manage the storage properly.